Spatial mapping and correlation between healthy home coverage and tuberculosis incidence in Malang district - Fatma Lidya Zulfa; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari; Rara Warih Gayatri; Erni Astutik (CV Rezki Media, 2025)
Background: According to the Ministry of Health, 91% of active tuberculosis (TB) cases in Indonesia occur in crowded and slum areas. The Healthy Homes Program under the Healthy Indonesia Indicators (2010) aims to improve housing conditions in such areas to meet health standards. Malang District, with the second-highest housing density in East Java, ranks fifth in TB cases, suggesting residential exposure as a contributing factor. Objectives: This study aims to map trends and examine the correlation between healthy home coverage and TB incidence in the Malang District Health Center Working Area 2019-2021. Methods: The study was conducted in January-April 2023 at the Malang District Health Office with a unit of analysis of 39 health centers. The variables of this study were the coverage of healthy homes and the incidence of BTA-positive pulmonary TB. The study used a mixed ecological study and Pearson correlation test with secondary data from the Malang District Health Office and BPS. Results: TB incidence showed a decreasing trend alongside increasing healthy home coverage. Nine health centers remained in high-incidence zones, and five exhibited poor housing coverage. Correlation analysis revealed a weak, negative relationship (r = -0.084). High TB incidence was still found in areas meeting healthy home criteria. Conclusions: The incidence rate of BTA-positive pulmonary TB in the working area of the Malang District Health Center showed a downward trend for 3 years. Future research using individual data and other specific risk factors that may influence TB incidence is recommended.